Endometriosis and Ovarian Cancer: Should we be worried? Five Cases Report and Literature Review - Silva Pereira, José; Nave, Mónica; Magro, Marta (Gazeta Médica, 2023)
Endometriosis is a chronic inflammatory disease caused by the presence of extra-uterine endometrial tissue that affects women of reproductive age. Although the etiology remains not totally elucidated, recent advances in molecular technology, especially the ability for whole genome sequencing, have gradually revealed both genetic and epigenetic backgrounds for the development of the disease. Endometriosis has been recognized as a precursor lesion for certain types of ovarian cancer (endometriosis-associated ovarian cancers - EAOC) and the knowledge of this malignant potential is of paramount importance to seek for predictive factors and to select patients at risk. We report five different EAOC cases in our recent clinical practice, in order to draw attention to this issue through a literature review, and to provide clinicians with tools to communicate accurately and effectively with patients with endometriosis about their risk of ovarian cancer.